Student Responses to the Nakhlah Method in Reading Arab Gundul: Tanggapan Siswa terhadap Metode Nakhlah dalam Membaca Arab Gundul - Rosida, Naylur Rohmatir; Ammar, Farikh Marzuki (Indonesian Journal of Islamic Studies, 2025)
General background: Mastery of Arabic is fundamental in Islamic education as it enables students to understand primary Islamic sources such as the Qur’an and Hadith. Specific background: Many students in Islamic boarding schools (pesantren) struggle to read Arab Gundul (Arabic script without diacritics), particularly due to difficulties in understanding nahwu and shorof. Knowledge gap: Although several teaching methods exist, limited studies have explored the effectiveness of the Nakhlah method—an innovative, song-based approach integrating Quantum Learning principles—on students’ reading competence. Aims: This study investigates the relationship between students’ responses to the Nakhlah method and their ability to read Arab Gundul in Tafsir Muyassar at Pondok Pesantren Tarbiyatul Iman Malang. Results: Using quantitative methods with Pearson correlation and simple linear regression on 17 students, findings reveal a significant relationship (p = 0.004 < 0.05) and a strong correlation (r = 0.655), with 42.9% of reading ability explained by the Nakhlah method. Novelty: This research presents empirical evidence of the pedagogical contribution of the Nakhlah method in improving Arabic literacy. Implications: The method can serve as an innovative alternative in Arabic language education within Islamic institutions. Highlights: Introduces the Nakhlah method as a song-based Arabic learning model. Demonstrates a strong correlation between method response and reading skill. Suggests innovation for improving Arabic instruction in pesantren. Keywords: Nakhlah Method, Arab Gundul, Arabic Literacy, Islamic Education, Quantum Learning